Potensi Penularan Covid-19 dalam Pembelajaran Pendidikan Jasmani Melalui Self Assessment Inarisk pada Siswa - Marwah Khairunnisa; Febi Kurniawan; Citra Resita (Peneliti.net, 2022)
Covid-19 is a virus that was previously undetected by humans, infected various groups and attacked the human lungs. Then it was declared a global pandemic that had an impact on the whole world, including Indonesia. One of the government's changes in adapting policies is in the field of education. Entering the post-pandemic period, new policy changes in the implementation of the education system returned to blended learning. One of the subjects that are feared to open new clusters for the spread of the COVID-19 virus is physical education because its implementation are without health protocols. This study intends to determine the magnitude of the potential transmission of the covid-19 virus by Self Assessment Inarisk, the research method used is descriptive quantitative with a percentage distribution table as a data translation. It was found that the potential for moderate infection was 47.7% in this study.